2021
DOI: 10.1101/2021.04.27.441642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simultaneous profiling of multiple chromatin proteins in the same cells

Abstract: Methods derived from CUT&RUN and CUT&Tag enable genome-wide mapping of the localization of proteins on chromatin from as few as one cell. These and other mapping approaches focus on one protein at a time, preventing direct measurements of co-localization of different chromatin proteins in the same cells and requiring prioritization of targets where samples are limiting. Here we describe multi-CUT&Tag, an adaptation of CUT&Tag that overcomes these hurdles by using antibody-specific barcodes to s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 43 publications
1
36
1
Order By: Relevance
“…Recently, technologies that profile two epigenetic modalities in single cells have been developed 21,22 . These technologies either use proteinA-Tn5 fusion pre-complexed with barcoded oligonucleotides or fusion 21 of Tn5 to HP1a to profile active and repressive chromatin simultaneously 22 . However, these technologies either lack the flexibility to profile various modalities, have lower sensitivity, might present cross-reactivity and/or have not been used to profile complex tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, technologies that profile two epigenetic modalities in single cells have been developed 21,22 . These technologies either use proteinA-Tn5 fusion pre-complexed with barcoded oligonucleotides or fusion 21 of Tn5 to HP1a to profile active and repressive chromatin simultaneously 22 . However, these technologies either lack the flexibility to profile various modalities, have lower sensitivity, might present cross-reactivity and/or have not been used to profile complex tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated the possibility to preload PA-Tn5 with antibodies to target different epigenetic marks simultaneously (Gopalan et al, 2021). We envision that this approach can also be applied to epigenomic MERFISH, making it possible to simultaneous map multiple distinct epigenetic marks in the same cells, for example marking promoter and enhancer activities by measuring H3K4me3 and H3K27ac activities simultaneously to provide a more comprehensive picture of enhancer activity and gene regulation within the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Reads were mapped to the hg38 genome using bwa-mem2 and fragment files created as described above for the NTT-seq datasets. Code to reproduce this analysis is available on GitHub: https://github.com/timoast/ multi-ct. We ran the CountFragments function in Signac to count the total number of fragments per cell for each multi-CUT&Tag assay, and retained cells with >200 total counts for further analysis, as described in the original publication (Gopalan et al 2021). For mixed-barcode fragments we counted ½ count to the total of each assay matching the pair of Tn5 barcodes.…”
Section: Multi-cutandtag Comparisonmentioning
confidence: 99%
“…2 Extended Data Figure 2. A) Total fragment counts per cell for multiCUT&Tag (Gopalan et al, 2021) and NTT-seq. Fragment counts on y-axis are on a log10 scale.…”
Section: Trajectory Analysismentioning
confidence: 99%